Maleic Anhydride Plant - Castillo, Mario D. (College of Engineering, 1964)
This plant design for the manufacture of maleic anhydride from benzene is designed with a capacity of twenty-five metric tone per twenty-four hour day. It requires a fixed capital investment of Php 1,601,000.00 and entails a total operating cost Php 10,500,000.00 per year.